1979
DOI: 10.1017/s0003356100023643
|View full text |Cite
|
Sign up to set email alerts
|

Production in mature corriedale ewes first mated at 7 to 11 or 18 months of age

Abstract: Production in 210 mature Corriedale ewes first mated between 7 and 11 or at 18 months of age was studied at Paysandu, Uruguay. Ewes were classified into one of the following five classes according to their oestrous and lambing performance in 1968: (1) reared a lamb; (2) lambed but lamb died; (3) mated but did not lamb; (4) oestrus detected by vasectomized ram, true mating deferred for 12 months; and (4) no oestrus, mating deferred for 12 months. Records on flock performance and mortality were kept from all ewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…The lack of a negative effect of hogget breeding on longevity has been also previously reported to at least 6 years of age (Cannon & Bath 1969;Baker et al 1978Baker et al , 1981Ponzoni et al 1979). These findings do TwinÁsingle, born as a twin but reared as a singleton; tripletÁtwin, born as a triplet but reared as a twin; tripletÁsingle, born as a triplet but reared as a singleton.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The lack of a negative effect of hogget breeding on longevity has been also previously reported to at least 6 years of age (Cannon & Bath 1969;Baker et al 1978Baker et al , 1981Ponzoni et al 1979). These findings do TwinÁsingle, born as a twin but reared as a singleton; tripletÁtwin, born as a triplet but reared as a twin; tripletÁsingle, born as a triplet but reared as a singleton.…”
Section: Discussionsupporting
confidence: 69%
“…Similarly, no negative effect on lamb weaning weight and apparent lamb survival has been reported previously (Cannon & Bath 1968;Baker et al 1978;Ponzoni et al 1979) and, indeed, Baker et al (1981) reported that those ewes that which were bred as hoggets weaned a heavier lamb in later years, with greater apparent survival.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Kenyon et al [ 1 ] recommended that, in New Zealand, a minimum live weight target should be 40 kg at breeding for Romney-type ewe lambs. To date, studies have focused on the effects of breeding ewe lambs on lifetime performance and efficiency compared to those not bred until 17–19 months of age [ 5 , 6 , 7 , 8 , 9 ], rather than the influence of their ewe lamb breeding live weight per se.…”
Section: Introductionmentioning
confidence: 99%